DYNAMICS AND TERRITORIAL LOCATION OF THE POPULATION OF NAVOVY REGION (Scientific journal of the Fergana State University, 2024)
Navoi region is one of the largest and smallest regions of our republic. This article uses statistical data to analyze regional differences in the region's demographics, population density and location. Population dynamics, urbanization processes, as well as the reasons for the high population growth of rural districts in the context of cities and regions have been studied. Rural districts are also divided into groups based on population density.